1999
DOI: 10.1002/(sici)1097-4547(19990401)56:1<54::aid-jnr7>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Propentofylline protects neurons in culture from death triggered by macrophage or microglial secretory products

Abstract: We recently demonstrated that conditioned medium (CM) from peritoneal macrophages or activated microglia triggers a predominantly apoptotic death in hippocampal neurons in culture. We tested the effects of propentofylline (ppf), an agent that is neuroprotective in focal ischemia and is also associated with reduced microglial antigen expression after insult. Ppf had no impact on the secretion of neurotoxin from microglia. However, ppf significantly attenuated the effects of macrophage and microglial conditioned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…2 Microglia are stimulated within hours after ischemia onset, 27,28 followed by upregulation of a variety of inflammatory factors. Microglia can generate similar substances under ischemia-like 3,29 and ischemic 30 conditions. Lynch et al 31 correlated microglial activation to BBB disruption in a model of 3-chlorpropanediol toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Microglia are stimulated within hours after ischemia onset, 27,28 followed by upregulation of a variety of inflammatory factors. Microglia can generate similar substances under ischemia-like 3,29 and ischemic 30 conditions. Lynch et al 31 correlated microglial activation to BBB disruption in a model of 3-chlorpropanediol toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 When activated, microglia undergo proliferation, chemotaxis, morphological alterations, and generate immunomodulatory molecules. Microglia release proteases, lipases, and glutamate 3,4 and are sensitive to hypoxia-and ischemia-like insults in vitro with a vulnerability greater than oligodendrocytes 5 and similar to or less than astrocytes, 6 depending on the model and species used. Their role in maintaining or interfering with BBB integrity in the context of ischemia is not well studied.…”
mentioning
confidence: 99%
“…However, it does not allow stating that microglial A 2A Rs play a key role in controlling the involvement of A 2A Rs in neuronal damage. In fact, studies with cultured cells showed that adenosine can directly attenuate neuronal damage caused by administration to neurons of medium from activated microglia cultures [98]. The development of a neuro-inflammatory process depends not only on microglia activation, but also on the participation of astrocytes (e.g., [288]) and neurons (e.g., [289]), as well as on the involvement of infiltrating myeloid cells (see [282,290,291]).…”
Section: A 2a Receptor Blockade Confers Robust Neuroprotectionmentioning
confidence: 99%
“…Microglia are among the first cells to respond to brain injury [199,200]. When stimulated, microglia undergo proliferation, chemotaxis, morphological alterations, and release of immunomodulatory molecules including proteases, lipases, glutamate and generate reactive oxygen species [201,202]. Blocking microglial activation may limit BBB disruption and reduce edema and hemorrhagic transformation.…”
Section: Minocyclinementioning
confidence: 99%